Strategi coping stress saat kuliah daring pada mahasiswa psikologi angkatan 2019 Universitas Andalas - Nezha Hanifah; Hany Lutfia; Ulfah Ramadhia; Rozi Sastra Purna (Jurnal Psikologi Tabularasa, 2020)
This study aims to determine the form of stress coping strategies taken by the '19 Psychology students when studying online. This type of research is a quantitative descriptive study using a survey method. The survey was carried out by distributing questionnaires related to stress coping strategies and the impact of stress coping on the 2019 Force Psychology Students of Andalas University while studying online. The subjects in this study were 84 Psychology Students Class of 2019 at Andalas University. The analysis techniques in this study were the percentage of stress coping, categorization of the level of coping stress, and the impact of stress coping in the Class of 2019, Andalas University while studying online. The research results obtained were as many as 61.9% of Psychology Students Class of 2019 Andalas University when studying online, most of them carried out stress coping strategies in the form of emotionally focused coping. The stress coping strategies of some of the Psychology students of class 19, Andalas University (51.2%), were in the quite good category. And most of Andalas University Class 19 Psychology Students (82.1%) felt a good impact after implementing stress coping strategies.